Localization of rDNA sites in holocentric chromosomes of three species of triatomines (Heteroptera, Triatominae). - Severi-Aguiar, Grasiela Dias de Campos; Oliveira, Maria Tercília Vilela de Azeredo [UNESP] (My University, 2005)
Chromatin organization in the holocentric chromosomes of three triatomines species was cytologically studied by fluorescent in situ hybridization with a 45S rDNA probe of Drosophila melanogaster to localize ribosomal genes. In Triatoma tibiamaculata, metaphases I showed telomeric highlights in a single, larger bivalent. In T. protacta, hybridization was detected in one of the telomeres of an autosomal chromosome. In T. platensis, there were highlights in a single, smaller chromosome (X chromosome). The results obtained did not agree with the expected localization of rDNA genes in the sex chromosomes of triatomines, as demonstrated by silver impregnation, and suggest that the chromosome reorganization that occurred in this group during evolution may be a more important mechanism involved in rDNA distribution.
Keywords: Drosophila protein; homeodomain protein; nubbin protein, Drosophila; ribosome DNA; transcription factor POU; animal; chromosome; chromosome banding pattern; chromosome NOR; classification; fluorescence in situ hybridization; genetics; male; metaphase; species difference; Triatominae; Animals; Chromosome Banding; Chromosomes; DNA, Ribosomal; Drosophila Proteins; Homeodomain Proteins; In Situ Hybridization, Fluorescence; Male; Metaphase; Nucleolus Organizer Region; POU Domain Factors; Species Specificity